2003
DOI: 10.1177/0272431602239132
|View full text |Cite
|
Sign up to set email alerts
|

Sociocognitive and Behavioral Correlates of a Measure of Prosocial Tendencies for Adolescents

Abstract: The present study was designed to examine the psychometric properties of a multidimensional measure of prosocial behaviors to use with early adolescents and middle adolescents. One hundred thirty-eight students ( X̄ age = 15.8 years; 80 girls; 70% White, non-Hispanic) from a public middle school and high school completed measures of prosocial moral reasoning, sympathy, perspective taking, aggression, ascription of responsibility, social desirability, verbal skills, and a revised prosocial tendencies measure (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
332
4
32

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 361 publications
(408 citation statements)
references
References 42 publications
26
332
4
32
Order By: Relevance
“…Because compliant prosocial behavior was not theorized to be related to sympathy (Carlo and Randall, 2002) and that previous research has suggested that compliant prosocial behaviors are not related to sympathy (Eisenberg et al, 1999), this relation between compliant prosocial behaviors and physical aggression warrants further attention. Similar to the present fi nding, Carlo et al (2003) reported a significant and negative relation between compliant prosocial behaviors and aggression in early adolescence. However, this same relation was nonsignifi cant in middle adolescence.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Because compliant prosocial behavior was not theorized to be related to sympathy (Carlo and Randall, 2002) and that previous research has suggested that compliant prosocial behaviors are not related to sympathy (Eisenberg et al, 1999), this relation between compliant prosocial behaviors and physical aggression warrants further attention. Similar to the present fi nding, Carlo et al (2003) reported a significant and negative relation between compliant prosocial behaviors and aggression in early adolescence. However, this same relation was nonsignifi cant in middle adolescence.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research, dire, emotional, and anonymous prosocial behaviors had no signifi cant relations with physical aggression (Carlo et al, 2003). Consequently, no mediation tests were conducted.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations